Saturn Anomalous Myriametric Radiation, a New Type of Saturn Radio Emission Revealed by Cassini. Issue 16 (19th August 2022) - Wu, S. Y.; Ye, S. Y.; Fischer, G.; Taubenschuss, U.; Jackman, C. M.; O'Dwyer, E.; Kurth, W. S.; Yao, S.; Yao, Z. H.; Menietti, J. D.; Xu, Y.; Long, M. Y.; et al.
Abstract: A new radio component namely Saturn Anomalous Myriametric Radiation (SAM) is reported. A total of 193 SAM events have been identified by using all the Cassini Saturn orbital data. SAM emissions are L‐O mode radio emission and occasionally accompanied by a first harmonic in R‐X mode. SAM's intensities decrease with increasing distance from Saturn, suggesting a source near Saturn. SAM has a typical central frequency near 13 kHz, a bandwidth greater than 8 kHz and usually drifts in frequency over time. SAM's duration can extend to near 11 hr and even longer. These features distinguish SAM from the regular narrowband emissions observed in the nearby frequency range, hence the name anomalous. The high occurrence rate of SAM after low frequency extensions of Saturn Kilometric Radiation and the SAM cases observed during compressions of Saturn's magnetosphere suggest a special connection to solar wind dynamics and magnetospheric conditions at Saturn. Plain Language Summary: This paper reports a new type of radio emission at Saturn. We name this emission "Saturn Anomalous Myriametric Radiation" (SAM). Due to the different morphological behavior of SAM emissions in the spectrogram, compared to the regularly observed narrowband emissions, SAM emissions are identified as a new radio component. We search for SAM events by using all the available data acquired by the Cassini spacecraft. A total of 193 SAM events are found and we summarized its characteristics. The spatial distribution of SAM shows a high latitude preference in occurrence. The observed intensities of SAM increase as the spacecraft approaches Saturn, suggesting a source near Saturn. The typical central frequency of SAM is near 13 kHz and the duration of SAM can extend to near 11 hr and even longer. The majority of the 193 SAM emissions are observed after the enhancement of the dominant Saturn radio emission Saturn Kilometric Radiation (SKR), which is deemed to be closely connected to the solar wind dynamics at Saturn. Therefore, SAM emissions are also possibly related to the conditions that cause the enhancement of SKR. This newly identified SAM emission may be used to study the magnetospheric dynamics of Saturn in the future. Key Points: A new radio component namely the Saturn Anomalous Myriametric Radiation (SAM) is reported The characteristics of SAM are given including its spatial distribution, typical frequency, bandwidth and time duration SAM shows a possible connection to the compression of the magnetosphere